Estratégias de fortificação de ferro na prevenção da anemia ferropriva em ambiente escolar: um estudo de revisão - Juliao, Laiz [UNIFESP] (2018)
Iron deficiency anemia is considered the most important nutritional disease in the world, especially in childhood. Within this context, the promotion of healthy habits, combined with the set of intervention strategies and programs in the school environment can combat and prevent anemia. The objective of this study was to systematically review the literature on strategies for the prevention of iron deficiency anemia in schoolchildren and the impact of these strategies on population health. The databases National Library of Medicine and the National Institutes of Health (PubMed), Scientific Electronic Library Online (SciELO), Google Scholar and manual search in the references selected for the review were searched. We included original studies describing results regarding prevention or treatment in preschoolers and schoolchildren who received some type of supplementation or interventions aimed at the prevention or treatment of iron deficiency anemia in school settings. Eight studies were selected that met the inclusion criteria. Interventions had a heterogeneous duration (2 to 24 months), and all of them used food fortification or iron water to improve hemoglobin levels and reduce the prevalence of anemia in children of pre-school age. We observed that, regardless of the dose, the time of administration and the strategy used, the results were positive and showed that fortification of foods in a school environment can be a potential facilitator for the prevention of anemia and improvement of children's hemoglobin levels in the first childhood, which are considered the most susceptible groups.